A lithium chloride-coated positive electrode material for improving an internal interface in an all-solid-state battery and a method of preparing the same

CN122968256APending Publication Date: 2026-10-23SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510487278.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

尽管有这样的优势,但它们相对较低的能量密度是显著提高电池整体性能的重要障碍

Benefits of technology

(1)本发明通过物理气相沉积法直接在正极材料表面包覆锂化氯化物,该锂化氯化物既可以作为锂离子导体又可以作为活性材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968256A_ABST
    Figure CN122968256A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of for improving the lithiumated chloride coated positive electrode material of internal interface in all-solid-state battery and its preparation method.The lithiumated chloride coated positive electrode material includes: positive electrode material matrix and the lithiumated chloride coating layer coated in the surface of positive electrode material matrix;Wherein, the molecular formula of the positive electrode material matrix is LiNi 1‑x‑y‑z Co x Mn y D z O2,0≤x,y,z≤1, D=Al or Mg, or Li 1+k Ni a Co b Mn c D d O2, k+a+b+c+d=1, 0≤a,b,c,d,k≤1, D=Al or Mg;The chemical formula of the lithiumated chloride coating layer is Li n MCl3, wherein 0≤n≤1, M=Fe, Ga, Al.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of all-solid-state lithium battery technology, and relates to a lithium chloride-coated cathode material for improving the internal interface of all-solid-state batteries under low stacking pressure and its preparation method. Background Technology

[0002] Battery energy storage technology, as a convenient energy storage technology that is gradually developing and gaining popularity, has been widely studied due to its high efficiency and environmental friendliness. However, with the broadening of research fields and the expansion of application scope, traditional liquid lithium batteries are facing challenges such as reduced driving range and safety stability.

[0003] Compared to traditional liquid batteries, all-solid-state batteries use solid electrolytes and are renowned for their superior safety and energy density, promising to revolutionize future energy storage technologies. Advances in solid electrolytes with low elastic modulus and cold-pressing capabilities are bringing all-solid-state batteries closer to commercialization. However, compared to traditional liquid electrolyte systems, chloride-based all-solid-state batteries still face significant challenges at the solid electrode / electrolyte interface. In particular, stress accumulation caused by volume changes in the positive electrode active material during cycling can induce the formation and propagation of cracks within the positive electrode, severely limiting its electrochemical performance.

[0004] To address the aforementioned issues—namely, the cracking and separation of the internal interface due to chemical-mechanical mismatch, which further leads to increased impedance and shortened battery life—two common strategies are currently employed to resolve these physical interface problems on the positive electrode side. The first is to prepare clay-like halide electrolytes, such as LiAlCl₂. 2.5 O 0.75(Nature Energy, 2023.8(11):p.1221-1228), xLiCl-GaF3(1≤x≤4)(ACS Energy Letters, 2021.6(5):p.2006-2015) and 2LiCl-xAlF3(1-x)GaF3(0.5≤x≤0.9)(Advanced Science, 2022.9(35):p.2204633). These clay-like halides exhibit excellent mechanical plasticity, enabling them to adapt to volume changes during cycling; however, these materials require further optimization in terms of cost and electrochemical stability. The second approach is to develop chloride-active cathode materials, such as VCl3 (Angewandte Chemie International Edition, 2023.62(13):p.e202217081) and FeCl3 (Nature Sustainability, 2024.7(11):p.1492-1500). They exhibit better mechanical compatibility with halide solid electrolytes in all-solid-state batteries. Despite these advantages, their relatively low energy density remains a significant obstacle to substantially improving overall battery performance. Therefore, a novel approach is urgently needed to enhance the electrochemical performance of batteries. Summary of the Invention

[0005] To address the aforementioned problems, this invention aims to provide a lithium chloride-coated cathode material and its preparation method for improving the internal interface in all-solid-state batteries. By directly coating the cathode material with lithium chloride using physical vapor deposition (PVD), stacking stress can be significantly reduced, and electrochemical performance and long-term cycle stability can be improved. This invention provides a simple, effective, and scalable strategy for optimizing the internal interface of the cathode, promoting the development and commercialization of cost-effective, high-performance all-solid-state batteries.

[0006] In a first aspect, the present invention provides a lithium chloride-coated cathode material, comprising: a cathode material substrate and a lithium chloride coating layer coated on the surface of the cathode material substrate; wherein the molecular formula of the cathode material substrate is LiNi. 1-x-y-z Co x Mn y D z O2, 0≤x, y, z≤1, D=Al or Mg, or Li 1+k Ni a Co b Mn c D d O2, k+a+b+c+d=1, 0≤a,b,c,d,k≤1,D=Al or Mg; the chemical formula of the lithium chloride coating is Li nMCl3, where 0≤n≤1, M=Fe,Ga,Al.

[0007] Preferably, the lithium chloride coating layer is formed by vacuum-sealing and heating a mixture of low-melting-point chloride and cathode material matrix powder, and then sublimating the gaseous chloride molecules into Li in the cathode material. + It is formed by lithiation.

[0008] Preferably, the melting point of the low-melting-point chloride is between 100 and 600°C; more preferably, the low-melting-point chloride is at least one of FeCl3, GaCl3, and AlCl3.

[0009] Secondly, the present invention provides a method for preparing the above-mentioned lithium chloride-coated cathode material, comprising the following steps: weighing low-melting-point chloride and cathode material matrix powder in proportion in a dry or inert atmosphere, and sealing them in a ball mill jar for ball milling to obtain a mixed powder; vacuum sealing the mixed powder and heating it to obtain the lithium chloride-coated cathode material.

[0010] In this invention, a physical vapor deposition method is used to directly deposit and lithiate low-melting-point chlorides on the surface of a cathode material, resulting in a cathode material coated with lithiated chlorides. Specifically, a mixture of low-melting-point chlorides and cathode material matrix powder is sealed in a vacuum quartz tube and heated to sublimate the relevant low-melting-point chlorides. The resulting gaseous chloride molecules diffuse to the surface of the cathode material, undergo heterogeneous nucleation and growth, and are simultaneously lithiated by the Lithium oxide in the cathode material. + Lithification is performed to form lithium chloride, ultimately yielding a cathode material coated with lithium chloride.

[0011] Preferably, the mass ratio of the low-melting-point chloride to the cathode material matrix powder is (1-20):100.

[0012] Preferably, the dry atmosphere has a dew point controlled below -30°C; the inert atmosphere is at least one of nitrogen, argon, and carbon dioxide.

[0013] Preferably, the parameters of the ball mill include: a ball-to-material ratio of (10-20):1, a ball mill rotation speed of 200-800 rpm, and a ball milling time of 10 minutes.

[0014] Preferably, the vacuum degree of the vacuum seal is 10. -1 ~10 -4 Pa.

[0015] Preferably, the heating temperature is 100–600°C, and the holding time is 0.5–10 h.

[0016] Thirdly, the present invention provides an all-solid-state battery cathode comprising the above-mentioned lithium chloride-coated cathode material.

[0017] Fourthly, the present invention provides an all-solid-state battery, comprising: a positive electrode; wherein the positive electrode comprises the above-mentioned lithium chloride-coated positive electrode material.

[0018] Beneficial effects: (1) The present invention directly coats the surface of the positive electrode material with lithium chloride by physical vapor deposition. The lithium chloride can be used as both a lithium-ion conductor and an active material. (2) Lithium chlorides, due to their low elastic modulus and high ionic conductivity, can effectively promote the growth of Lithium chlorides. + Transport at the cathode interface inhibits crack propagation, thereby stabilizing the internal interface of the cathode and improving the electrochemical performance of the all-solid-state battery. Furthermore, this lithium chloride-coated cathode enables the all-solid-state battery to cycle stably under low stacking pressure. (3) The lithium chloride-coated cathode material prepared by this method has high element abundance and low price. At the same time, the preparation process is simple and highly reproducible, making it suitable for large-scale industrial production. Attached Figure Description

[0019] Figure 1 In the preferred embodiment 1 of the present invention, LiNi coated with lithium ferric chloride (LFC) is formed in situ. 0.8 Co 0.1 Mn 0.1 X-ray diffraction pattern of O2(NCM811) ternary cathode material (F@NCM811); Figure 2 The images show a scanning electron microscope (SEM) image (ad) and an X-ray energy dispersive spectroscopy (EDS) image (eg) of the F@NCM811 material in the preferred embodiment 1 of the present invention. Figure 3 The charging and discharging curves of the F@NCM811-based all-solid-state battery in the preferred embodiment 1 of the present invention and the uncoated NCM811 battery in Comparative Example 1 are shown; wherein (a) is the first charge and discharge curve of the battery, and (b) is the charge and discharge curve of the battery under different cycles. Detailed Implementation

[0020] To further illustrate the invention's content, features, and practical effects, the invention will be described in detail below with reference to embodiments. It should be noted that the modification methods of the invention are not limited to these specific implementation methods. Equivalent substitutions and modifications made by those skilled in the art based on their reading of the invention's content, without departing from the spirit and essence of the invention, are also within the scope of protection claimed by this invention.

[0021] First, the present invention provides a lithium chloride-coated cathode material, comprising: a cathode material substrate and a lithium chloride coating layer coated on the surface of the cathode material substrate; wherein the molecular formula of the cathode material substrate is LiNi. 1-x-y-z Co x Mn y D z O2, 0≤x, y, z≤1, D=Al or Mg, or lithium-rich NCMD type cathode material Li 1+ k Ni a Co b Mn c D d O2, k+a+b+c+d=1, 0≤a, b, c, d, k≤1, D=Al or Mg; the lithium chloride coating layer is formed by vacuum sealing and heating a mixture of low-melting-point chloride and positive electrode material matrix powder, and then sublimating the gaseous chloride molecules into Li in the positive electrode material. + It is formed by lithium modification. The chemical formula of the lithium chloride coating layer is Li. n MCl3, where 0≤n≤1, M=Fe, Ga, Al, etc. The lithium chloride-coated cathode material possesses a low elastic modulus. During mixing and cold pressing, the lithium chloride effectively adheres to the chloride solid electrolyte, optimizing the spatial distribution of the solid electrolyte. During cycling, it can more effectively suppress the formation and propagation of NCM / solid electrolyte interface cracks through the plastic deformation of the chloride solid electrolyte, thereby improving the internal interface of the cathode, rather than achieving this through providing higher stacking pressure.

[0022] In this invention, low-melting-point chlorides (such as FeCl3, GaCl3, etc.) are deposited on NCMD-type cathode materials (LiNi) using physical vapor deposition (PVD). 1-x-y-z Co x Mn y D z O2, 0≤x,y,z≤1, D=Al or Mg)(e.g. LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM111, etc.) or lithium-rich NCMD type cathode materials (Li 1+k Ni a Co b Mn c D dO2 (k+a+b+c+d=1, 0≤a, b, c, d, k≤1, D=Al or Mg)) is deposited on the surface and lithiated, ultimately forming lithium chloride-coated cathode particles. The lithium chloride coating is achieved by sealing a mixture of low-melting-point chlorides (such as FeCl3, GaCl3, etc.) and NCMD in a vacuum quartz tube and heating it to sublimate the low-melting-point chlorides. The resulting gaseous chloride molecules diffuse to the NCMD surface, undergoing nucleation and growth while being absorbed by the Li in the NCMD. + Lithification is performed to form a lithium chloride-coated cathode material. The preparation method of this invention is simple, highly reproducible, and the prepared lithium chloride-coated cathode material can significantly improve the electrochemical performance of all-solid-state batteries and reduce the stacking pressure of all-solid-state batteries.

[0023] The following exemplarily illustrates the preparation method of the lithium chloride-coated cathode material provided by the present invention.

[0024] In a dry or inert atmosphere, low-melting-point chloride and cathode material matrix powder are weighed in proportion and sealed in a ball mill jar for ball milling to obtain a mixed powder.

[0025] In an optional embodiment, the mass ratio of the low-melting-point chloride to the cathode material matrix powder is (1-20):100.

[0026] In an optional embodiment, the drying process involves controlling the dew point to below -30°C; the inert atmosphere is at least one of nitrogen, argon, and carbon dioxide.

[0027] In an optional embodiment, the parameters of the ball mill include: a ball-to-material ratio of (10-20):1, a ball mill rotation speed of 200-800 rpm, and a ball milling time of 10 minutes.

[0028] The mixed powder is vacuum sealed and heated to a specified temperature in a muffle furnace or tube furnace, and then cooled to room temperature to obtain the lithium chloride-coated cathode material.

[0029] In an optional embodiment, the vacuum level of the vacuum seal is 10. -1 ~10 -4 Pa. The heating temperature is 100–600°C, and the holding time is 0.5–10 h. If the heating temperature is too high, the deposition rate of lithium chloride will be too fast, resulting in larger coated particles; if the heating temperature is too low, the chloride will not be able to vaporize, thus failing to form a coated morphology.

[0030] This invention controls the deposition morphology of the lithium chloride coating layer on the NCMD surface by controlling the mass ratio of low-melting-point chloride to cathode material matrix powder, heating temperature, and time. If the mass ratio of low-melting-point chloride to cathode material is too small, the chloride coating is insufficient, resulting in poor battery performance and insignificant effect; if the mass ratio is too large, the coating layer is too thick, leading to insufficient discharge capacity of the NCMD material. If the heating temperature is too low, the chloride cannot be vaporized; if the heating temperature is too high, the deposited chloride grows too quickly, resulting in large particles. If the holding time is too short, the coating is incomplete; if the holding time is too long, the particles are also large. Too low a ball-to-material ratio and ball milling speed in ball milling will result in insufficient ball milling, leaving some NCMD particles without a coating layer; too high a ball-to-material ratio and ball milling speed will cause the raw material particles to break. If the vacuum seal is too low, the chloride will not easily vaporize, resulting in insufficient chloride coating on the NCMD particles.

[0031] The present invention also provides an all-solid-state battery cathode comprising the above-mentioned lithium chloride-coated cathode material.

[0032] This invention also provides an all-solid-state battery, comprising: a positive electrode; the positive electrode comprising the aforementioned lithium chloride-coated positive electrode material. The lithium chloride-coated positive electrode material is assembled into an all-solid-state battery, and its performance is tested. Phase analysis is performed using X-ray diffraction (XRD); morphology analysis is performed using field emission scanning electron microscopy (SEM); and energy-dispersive X-ray spectroscopy (EDS) is used to observe the microstructure of the particles. Electrochemical performance testing: test temperature 25℃, charge / discharge rate 0.1C, charge / discharge voltage range 2.38~3.68V (vs. Li). + / Li-In), the test was maintained for 200 cycles.

[0033] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below.

[0034] Example 1

[0035] The LiNi provided in this embodiment 1 0.8 Co 0.1 Mn 0.1A method for preparing O2(NCM811) cathode material coated with lithium-ion ferric chloride includes: weighing FeCl3 and single-crystal NCM811 at a mass ratio of 2:100 in an argon-atmosphere glove box, sealing them in a ball mill jar, and ball milling for 10 minutes at a ball-to-material mass ratio of 10:1 and a rotation speed of 200 rpm to obtain a mixed powder; transferring the mixed powder to a quartz tube for vacuum sealing, with a vacuum degree of approximately 10... -3 To prevent FeCl3 volatilization during the tube sealing process, the bottom of the quartz tube was cooled with ice. Finally, the sealed quartz tube was placed in a muffle furnace and heated to 200℃ at a rate of 5℃ / min, and held for 2 hours to obtain LFC-coated NCM 811 (F@NCM811) cathode material. Chloride solid electrolyte, lithium phosphorus sulfide chlorine (LPSC), and F@NCM811 cathode material were sequentially placed in a 10mm diameter solid-state battery mold and held at 370MPa for 1 minute. Subsequently, a 10mm diameter Li-In anode was sequentially placed on the LPSC side, and finally, a pressure of 2–5MPa was applied to the entire battery to test its electrochemical performance. The test conditions were: test temperature 25℃, charge / discharge rate 0.1C, and charge / discharge voltage range of 2.38–3.68V (vs. Li). + / Li-In), the test was maintained for 200 cycles.

[0036] The preparation process of Examples 2-18 is the same as that of Example 1. Please refer to Table 1 for the raw material ratio and preparation parameters.

[0037] Comparative Example 1

[0038] Using LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary cathode material, without coating treatment.

[0039] Comparative Example 2

[0040] Using Li 1.2 Ni 0.15 Co 0.1 Mn 0.55 O2 ternary cathode material, without coating treatment.

[0041] Comparative Example 3

[0042] Using LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 ternary cathode material, without coating treatment.

[0043] Table 1 lists the relevant raw materials and mass ratios, preparation parameters and performance data for Examples 1-18 and Comparative Examples 1-3.

[0044] Table 1:

[0045] Figure 1 In the preferred embodiment 1 of the present invention, LiNi coated with lithium ferric chloride (LFC) is formed in situ. 0.8 Co 0.1 Mn 0.1 X-ray diffraction pattern of O2(NCM811) ternary cathode material (F@NCM811). The figure shows a characteristic peak corresponding to the orthorhombic phase Li2FeCl4 (PDF#84-1532) observed at 2θ = 34.6°, while no diffraction peak of the raw material FeCl3 was detected at 2θ = 33.4°. FeCl3 is a hexagonal phase, and its standard card is PDF#01-1059. This result indicates that the hexagonal FeCl3 underwent lithiation and phase transition during PVD, ultimately forming lithium-containing Li. n FeCl3 (LFC, 0≤n≤1).

[0046] Figure 2 The images show scanning electron microscope (SEM) (ad) and X-ray energy dispersive spectroscopy (EDS) (eg) images of the F@NCM811 material in the preferred embodiment 1 of the present invention. The SEM data shows that island-like lithium-ionized ferric chloride uniformly coats the NCM811 cathode material on its surface. The EDS data of F@NCM811 shows that Fe and Cl signals are located on the NCM811 surface, while O and Ni signals originate from the underlying NCM811 particles.

[0047] Figure 3 The figures show the charge-discharge curves of the F@NCM811-based all-solid-state battery in the preferred embodiment 1 of this invention and the uncoated NCM811 battery in Comparative Example 1. As shown in Figure (a), the discharge capacity of the F@NCM-based battery is 188.6 mAh / g, while that of the NCM-based battery is only 185.4 mAh / g. There is also a difference in initial efficiency; the F@NCM-based battery achieves a coulombic efficiency of 90.9% in its first cycle, while the NCM-based battery only achieves 87.6%. As shown in Figure (b), long-term cycle testing at 25°C and 0.1C shows that after 200 cycles, the F@NCM811-based battery retains 90.2% of its capacity, significantly higher than the 77.9% retention rate of the uncoated NCM811 battery in Comparative Example 1.

Claims

1. A lithium chloride-coated cathode material, characterized in that, include: A cathode material substrate and a lithium chloride coating layer covering the surface of the cathode material substrate; wherein the molecular formula of the cathode material substrate is LiNi. 1-x-y- z Co x Mn y D z O2, 0≤x, y, z≤1, D=Al or Mg, or Li 1+k Ni a Co b Mn c D d O2, k+a+b+c+d=1, 0≤a, b, c, d, k≤1, D=Al or Mg; the chemical formula of the lithium chloride coating is Li n MCl3, where 0≤n≤1, M=Fe,Ga,Al.

2. The lithium chloride-coated cathode material according to claim 1, characterized in that, The lithium chloride coating is produced by vacuum-sealing and heating a mixture of low-melting-point chloride and cathode material matrix powder, allowing the sublimated gaseous chloride molecules to be coated by the Lithium chloride in the cathode material. + It is formed by lithiation.

3. The lithium chloride-coated cathode material according to claim 1 or 2, characterized in that, The melting point of the low-melting-point chloride is between 100 and 600°C; preferably, the low-melting-point chloride is at least one of FeCl3, GaCl3, and AlCl3.

4. A method for preparing a lithium chloride-coated cathode material according to any one of claims 1-3, characterized in that, The process includes the following steps: in a dry or inert atmosphere, weigh low-melting-point chloride and cathode material matrix powder in proportion, and seal them in a ball mill jar for ball milling to obtain a mixed powder; vacuum seal the mixed powder and heat it to obtain the lithium chloride-coated cathode material.

5. The preparation method according to claim 4, characterized in that, The mass ratio of the low-melting-point chloride to the cathode material matrix powder is (1-20):

100.

6. The preparation method according to claim 4 or 5, characterized in that, The dry atmosphere has a dew point controlled below -30°C; the inert atmosphere is at least one of nitrogen, argon, and carbon dioxide.

7. The preparation method according to any one of claims 4-6, characterized in that, The parameters of the ball mill include: a ball-to-material ratio of (10-20):1, a ball mill rotation speed of 200-800 rpm, and a ball milling time of 10 minutes.

8. The preparation method according to any one of claims 4-7, characterized in that, The vacuum level of the vacuum seal is 10. -1 ~10 -4 Pa; The heating temperature is 100–600℃, and the holding time is 0.5–10h.

9. A positive electrode for an all-solid-state battery, characterized in that, The cathode material comprising any one of claims 1-3, including the lithium chloride-coated cathode material.

10. An all-solid-state battery, characterized in that, include: The positive electrode comprises the lithium chloride-coated positive electrode material according to any one of claims 1-3.